A study on the challenges faced by hr professionals during pandemic and in post pandemic - SIVANANDAM, DR. PRASANNA; KUMAR R, MR ASHWATH (The journal of contemporary issues in business and government, 2020)
The terms ’Human resource management’ and ’Human resources’ have generally supplanted the term ’personnel management’ and furthermore consider it as a cycle which is associated with dealing with the associations. Human Resource Management is the way toward enlisting the up-and-comers, choosing the correct candidate for particular job, accepting representatives, providing orientation, training and development, assessing the presentation of workers, choosing remuneration and giving advantages, propelling workers, keeping up legitimate relations with workers and their worker’s organizations, motivating employees , ensuring employees safety, welfare and health measures of the employees. The objectives of HR in an organisation are as follows: Understand the scope of human resource management (HRM),explain what human resource management is and how it relates to the management process. Many organisations are managing with the Covid-19 coronavirus widespread by ordering or empowering representatives work from domestic all over the world. As the coronavirus spreads, working from domestic is the unused typical for specialists. Representative help programs (EAPs) will be important sources of organizational bolster to help representatives going through challenging times and progress their well- being and resilience. Again, a look on the Net of Science uncovers exceptionally few thoughts about EAPs in Asian nations. This activated organizational reactions such as decentralizing their operations and moving workers out of base camp, particularly in the event that found in huge urban ranges. This in turn driven to organizations re-examining their recompense arrangements to superior reflect emolument levels related with the nearby work showcase. A survey has been collected from the HR professionals from various organisations regarding the various challenges that have been faced by them during pandemic and in post pandemic and to find out the most influencing factors among the various challenges.